The Implementation of Badiuzzaman Said Nursi's Concept of Hope in Addressing the Crisis of Public Trust in Indonesian Politics - Huringiin, Nabila; Al Faruqi, Achmad Reza Hutama; Nurhalisa, Siti (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This research aims to analyze how the concept of hope proposed by Badiuzzaman Said Nursi can be implemented to address the crisis of public trust in politics in Indonesia. The crisis of political trust in Indonesia has become one of the issues hindering the development of democracy and public participation. Badiuzzaman Said Nursi, through his works, emphasizes the importance of hope as a spiritual force that can revive the spirit of social and political awakening in society. This study conducts a literature review of Nursi's concept of hope, along with a qualitative analysis of the factors influencing the crisis of political trust in Indonesia. The research also connects this concept with the Indonesian political context, exploring its relevance in offering solutions to political apathy and public disillusionment. The findings of this research conclude that Said Nursi addressing the crisis of trust in politics demands not only structural reforms but also a focus on spiritual and moral development. The findings of this study are expected to provide both theoretical and practical contributions to the development of a more optimistic and constructive political discourse in Indonesia, with the hope that the spiritual values taught by Nursi can help revitalize public trust in the political system.